Long-time state employee retires (Raton Range Raton, New Mexico, 1989)
Newspaper Article on Alex G. Lucero's retirement from the Motor Transportation Division of the Enforcement Bureau Division of New Mexico.
Master list item #: 13
File location is in the Raton File Cabinet
Keywords: Lucero, Alex G; Maestas, Rudy; Lucero, Theresa; Lucero, Sharon; Lucero, Lynda; Motor Transportain Division; New Mexico Department of Transportation; Local History; Biography; Life and Customs; Retirement; Family; Fishing; Raton, New Mexico; Jal, New Mexico; Pojoaque, New Mexico; Clayton, New Mexico